A comprehensive study on bisphenol A and estrogenic activity in the Paraíba do Sul River, São Paulo, Brazil - Roledo, Cely [UNESP]; França, Daniela Dayrell; dos Santos Feitosa, Ingrid Ruanna; Quinaglia, Gilson Alves; Montagner, Cassiana Carolina; Roubicek, Deborah Arnsdorff; dos Reis, Adriano Gonçalves [UNESP] (IWA Publishing, 2024)
In recent decades, contaminants of emerging concern (CECs) in aquatic environments have garnered significant attention due to their adverse effects on ecosystems and human health. Among these CECs, bisphenol A (BPA) is a major concern because of its widespread use and endocrine-disrupting properties. Brazil’s urbanization and industrial growth have led to significant pollution challenges, primarily due to inadequate sewage infrastructure and untreated domestic wastewater being discharged into rivers, contributing to the presence of emerging contaminants in surface waters. This study assessed BPA contamination and estrogenic activity in the Paraíba do Sul River in São Paulo State, Brazil. BPA was detected in 50% of the samples, with concentrations ranging from 11.1 to 116.9 ng L-1. The estrogenic activity assay also showed positive results in 50% of the samples, ranging from 0.12 to 1.36 ng L-1 of estradiol-equivalent, indicating the presence of multiple compounds contributing to estrogenic effects. This underscores the need for a comprehensive approach to monitoring water quality. The water quality index (WQI) revealed compromised water quality at the studied sites, particularly during the rainy season. The correlation between the WQI, BPA, and estrogenic activity parameters suggests that endocrine-disrupting compounds significantly impact water quality, exacerbated by inadequate wastewater treatment infrastructure.
Keywords: BLYES; BPA; contaminants of emerging concern; endocrine disruptor; water quality index